2016
DOI: 10.1161/jaha.115.002248
|View full text |Cite
|
Sign up to set email alerts
|

Simple Renal Cysts as Markers of Thoracic Aortic Disease

Abstract: BackgroundThoracic aortic aneurysm is usually a clinically silent disease; timely detection is largely dependent upon identification of clinical markers of thoracic aortic disease (TAD); (bicuspid aortic valve, intracranial aortic aneurysm, bovine aortic arch, or positive family history). Recently, an association of simple renal cysts (SRC) with abdominal aortic aneurysm and aortic dissection was established. The aim of our study was to evaluate the prevalence of SRC in patients with TAD in order to assess whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
2
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 44 publications
2
21
2
5
Order By: Relevance
“…Ziganshin et al 15 demonstrated a prevalence of renal cysts of 15.3% in the control group, compared to the prevalence of 44.9% observed in our control group. This difference may be explained by the average age of our control group, which was significantly higher (63.5 vs. 41.4 years).…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Ziganshin et al 15 demonstrated a prevalence of renal cysts of 15.3% in the control group, compared to the prevalence of 44.9% observed in our control group. This difference may be explained by the average age of our control group, which was significantly higher (63.5 vs. 41.4 years).…”
Section: Discussioncontrasting
confidence: 73%
“…Recently, Ziganshin et al 15 demonstrated that patients with aortic aneurysm had 2.8 times greater prevalence of renal cyst compared to the control group. Ziganshin et al 15 demonstrated a prevalence of renal cysts of 15.3% in the control group, compared to the prevalence of 44.9% observed in our control group.…”
Section: Discussionmentioning
confidence: 99%
“…We found that in all four of these groups of patients with thoracic aortic disease, the prevalence of SRC was significantly higher than in our control group and higher than reported for the general population ( Figure 7A) (34). The prevalence of SRC was also higher in the thoracic aortic disease group when broken down by age groups, a valuable observation since age is an important contributor to the natural history of SRC ( Figure 7B) (34). Moreover, the male preponderance for SRC that is seen in the general population (on average 2:1 male to female ratio) is lost in all four groups of patients with disease of the thoracic aorta ( Figure 7C) (34).…”
Section: Simple Renal Cysts (Src)contrasting
confidence: 62%
“…Another study found a higher prevalence of renal cysts in patients with Marfan syndrome compared to non-Marfan controls (33). A study from our group evaluated the frequency of SRC in patients with ascending and descending aortic aneurysm, as well as Type A and Type B dissection (34). We found that in all four of these groups of patients with thoracic aortic disease, the prevalence of SRC was significantly higher than in our control group and higher than reported for the general population ( Figure 7A) (34).…”
Section: Simple Renal Cysts (Src)mentioning
confidence: 99%
See 1 more Smart Citation